1996
DOI: 10.1177/00220345960750020401
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Edge-losses in Reflectance Measurements of Pigmented Maxillofacial Elastomer

Abstract: Edge-losses occur during reflectance measurements of pigmented maxillofacial elastomer when light is scattered within a sample beyond that part of the surface exposed to the observation system of the optical device. A custom sample-holder is presented which redirects light that would not be measured during conventional reflectance measurement back into the sample. The amount of edge-loss occurring within thin layers of maxillofacial elastomer with tan pigment on black-and-white backings was found to depend on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 10 publications
0
55
0
3
Order By: Relevance
“…However, it has been demonstrated that both spectrophotometric and colorimetric devices can suffer edge loss effects, which happen when a device with a small window measuring a transparent material results in light scattering to the edge of the sample without being detected. Edge-loss is affected by the illuminating beam size and direction, observation geometry, thickness of the specimen, and the reflectance of the backing [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that both spectrophotometric and colorimetric devices can suffer edge loss effects, which happen when a device with a small window measuring a transparent material results in light scattering to the edge of the sample without being detected. Edge-loss is affected by the illuminating beam size and direction, observation geometry, thickness of the specimen, and the reflectance of the backing [20].…”
Section: Introductionmentioning
confidence: 99%
“…36 This edge-loss effect could affect the accuracy of the measurement. 37 A method to minimize the edge-loss effect by the use of plasticine was introduced, 38 producing higher TP values than those obtained by the conventional method. 39 In this study, as the specimen size was much larger than the colorimeter window, the edge-loss effect could be ignored.…”
Section: E86mentioning
confidence: 99%
“…[12][13][14] Many studies have been conducted in the field of prosthetics, where the effect is particularly apparent and can easily result in esthetic issues. 12,[14][15][16][17][18] Edge loss is also known to exert an influence when colorimetry is performed on human skin. 13 Studies of edge loss have shown that the choices of illumination area and measurement area exert major influences on the magnitude of colorimetry results.…”
Section: Introductionmentioning
confidence: 99%